Thirty Years of Research on the Application of Cybernetic Methods in Fisheries and Aquaculture Technology - Jens G. Balchen (Modeling, Identification and Control, 2000)
The paper surveys the research activities at the Department of Engineering Cybernetics, Norwegian University of Science and Technology, Trondheim, Norway, in the application of cybernetic principles in fisheries technology, aqua-culture technology and ocean ranching during the period 1969-1999. It is believed that the results obtained in these activities will have an impact upon the future developments in one of the most important sectors of the Norwegian economy. Numerous reports and publications are listed in the comprehensive bibliography.